Pathways of change : Socio-cultural change among the highlanders of western New Guinea - Anton Ploeg (pacific-credo Publications, 2020)
This monograph is a comparative study of eight ways of life of highlanders in West Papua. It consists of ten sections: an introduction, a conclusion and eight ethnographic chapters, each dealing with a separate way of life. I chose this presentation since I wanted to make clear the individuality of each of them. In the book I attempt to trace the changes in these ways of life as they were occurring just previous to the settlement of colonial outsiders. This attempt proved feasible since for seven of them first contact accounts are available.